The Constitutionality of Federal Jurisdiction-Stripping Legislation and the History of State Judicial Selection and Tenure - FitzPatrick, Brian T. (2012)
Few questions in the field of Federal Courts have captivated scholars like the question of whether Congress can simultaneously divest both lower federal courts and the U.S. Supreme Court of jurisdiction to hear federal constitutional claims and thereby leave those claims to be litigated in state courts alone. Such a divestiture is known today as “jurisdiction stripping,” and, despite literally decades of scholarship on the subject, scholars have largely been unable to reconcile two widely held views: jurisdiction stripping should be unconstitutional because it deprives constitutional rights of adjudication by independent judges and jurisdiction stripping is nonetheless perfectly consistent with the text and original understanding of the Constitution. In this article, I show how the scholarly impasse that has pitted constitutionalism and judicial independence on the one hand versus text and history on the other can be overcome. In particular, I show that something important has changed in the years since the Constitution was ratified: the gap between the independence of state and federal judges. At the time of the founding, much like their federal counterparts, no state judges were elected and the vast majority of them enjoyed life tenure. Precisely the opposite is true today. As such, the consequences of depriving federal courts of jurisdiction to hear constitutional claims were much different then than they are today. Because state courts were the background against which Article III of the Constitution was written and ratified, these changes enable the answer to the question of whether jurisdiction stripping is constitutional to change as well. In other words, just because jurisdiction stripping was constitutional in 1789 does not mean it must be constitutional today, and it does not mean we must ignore the original understanding of the Constitution to reach that conclusion. The history I have uncovered in this article has the potential to reshape many other jurisdictional doctrines of the federal courts